Reducing time headway for platooning of connected vehicles via V2V communication. (May 2019) - Bian, Yougang; Zheng, Yang; Ren, Wei; Li, Shengbo Eben; Wang, Jianqiang; Li, Keqiang
Highlights: A consistent definition of desired inter-vehicle distances is introduced. Lower-triangular structures of the system matrix are used for stability analysis. The lower bound of employable time headway is derived for string stability. The lower bound of time headway can be reduced by following more predecessors. Abstract: In a platoon of connected vehicles, time headway plays an important role in both traffic capacity and road safety. It is desirable to maintain a lower time headway while satisfying string stability in a platoon, since this leads to a higher traffic capacity and guarantees the disturbance attenuation ability. In this paper, we study a multiple-predecessor following strategy to reduce time headway via vehicle-to-vehicle (V2V) communication. We first introduce a new definition of desired inter-vehicle distances based on the constant time headway (CTH) policy, which is suitable for general communication topologies. By exploiting lower-triangular structures in a time headway matrix and an information topology matrix, we derive a set of necessary and sufficient conditions on feedback gains for internal asymptotic stability. Further, by analyzing the stable region of feedback gains, a necessary and sufficient condition on time headway is also obtained for the string stability specification. It is proved that a platoon can be asymptotically stable and string stable when the time headway is lower bounded. Moreover, this bound can be reduced by increasing the number of predecessors. These results explicitly highlight the benefits of V2V communication on reducing time headway for platooning of connected vehicles.